THE CONDITIONALITY OF THE EMOTIONAL INTELLIGENCE INFLUENCE ON ADAPTABILITY, PSYCHOLOGICAL WELL-BEING AND SUBJECTIVE SUCCESS (DURING THE PANDEMIC) - Sanko, Karina (PSYCHOLOGICAL JOURNAL, 2021)
The article studies the importance of emotional intelligence in various social situations. It emphasizes that a person’s behaviour is determined both by personal traits and a social situation. The foreign experience in studying the influence of social situations on emotional intelligence manifestations and its components is analysed. The foreign view takes into account, in fact, not the characteristics of the social situation experienced by a person, but the characteristics (context) of the social environment. The article presents also national scientists’ views on this issue, according to which a social situation and its role is considered via "emotionogenicity" of the situation for the individual, and also the question appears on classification of social situations. Manifestations of emotional intelligence and its components should be studied theoretically and empirically in the context of a person’s emotional experience and "physical living" in difficult life circumstances. The author defines the qualitative indicators of emotional intelligence and its components that can become certain markers of the psychological quality of difficult situation experiencing. A person’s psychological well-being, adaptability and subjective success can be such qualitative indicators revealing understanding by a person of experienced difficult life circumstances. Namely, these psychological indicators indicate the quality of the situation experiencing and the role of the emotional intelligence components in adaptability, ensured psychological well-being and a sense of subjective success. The empirical analysis of the proposed indicators give an understanding of whether a person is fully psychologically and qualitatively living the circumstances and what the role of emotional intelligence is. The theoretical model of emotional intelligence influence on the psychological indicators of a person’s life quality, depending on a social situation, is presented. The model demonstrates the influence of emotional intelligence and its components on adaptability, psychological well-being and subjective success depending on social situations, and vice versa. This model should be applied for the empirical study on the mutual influence of emotional intelligence on the above indicators; its novelty and importance for understanding of the social context is emphasizes. The constructed regression models are examined to determine connections and assert that the feelings of psychological well-being, adaptability and subjective success in a difficult situation are determined by the corresponding components of emotional intelligence, in particular, during the pandemic. In such difficult life situation as the pandemic, emotional intelligence ensures adaptability, psychological well-being and subjective success. The constructed regression models indicate that emotional intelligence components influence differently on particular characteristics during the pandemic, in particular, adaptability is ensured indirectly by controlling emotions and developed interpersonal emotional intelligence; psychological well-being depends on such emotional intelligence components as understanding one’s emotions, empathizing with unhappiness, and control over expressions; the feeling of subjective success during the pandemic is mediated by understanding of one’s own emotions and empathizing with unhappiness. In such difficult life situation as the pandemic, the components ensuring both psychological well-being and subjective success are the understanding of one’s own emotions and empathy for unhappiness, which indicates the importance of a contact with one’s own emotions and collective inclusion into the difficult situation. And the resulting regression model for adaptability includes completely different components of emotional intelligence, namely, emotional management and interpersonal emotional intelligence, which shows the focus on interpersonal interaction.